2013
DOI: 10.1021/om400654c
|View full text |Cite
|
Sign up to set email alerts
|

A New Route to Phosphaalkene Chelate Complexes: SET Deoxygenation of Oxaphosphirane Complexes Followed by Intramolecular CO Substitution

Abstract: Contentsp.2 Crystal data for 1a,b p.3 Crystal structure determination and molecular structure of 1a (Figure S1) p.4 Crystal structure determination and molecular structure of 1b (Figure S2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…31 P­{ 1 H} NMR spectroscopy of the reaction mixture showed a signal at 195.3 ppm ( 1 J W,P = 255.1 Hz) which is in the expected range for complex 7 . Unfortunately, complexes 3 and 7 could not be separated due to very similar solubilities, and further attempts to use column chromatography were met with limited success due to their instability on the solid phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 P­{ 1 H} NMR spectroscopy of the reaction mixture showed a signal at 195.3 ppm ( 1 J W,P = 255.1 Hz) which is in the expected range for complex 7 . Unfortunately, complexes 3 and 7 could not be separated due to very similar solubilities, and further attempts to use column chromatography were met with limited success due to their instability on the solid phase.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of monocyclic oxaphosphirane complexes IV , the synthetic breakthrough came with the advent of Li/Cl phosphinidenoid complexes as P 1 building blocks due to their high reactivity toward aldehydes and ketones combined with functional group tolerance. , For example, studies on acid-induced ring opening (i) and ring expansion (ii) have demonstrated that they are valuable building blocks for unusual heterocyclic P-ligands and, hence, deserve further investigations. Furthermore, the possibility to remove the ring oxygen atom via a reductive single electron transfer (SET) reaction using Ti­(III) reagents is of particular interest as it had opened a new route to end-on phosphaalkene complexes …”
mentioning
confidence: 99%
“…12a: 1 H NMR (CDCl 3 ) δ 0.30 (s, 9 H, SiMe 3 ), 0.34 (s, 9 H, SiMe 3 ), 2.25 (d, 1 H, 2 J P,H = 4.0 Hz, CH), 3.57 (d, 1 H, 2 J H,H = 15.0 Hz, CH 2 ), 3.85 (dd, 1 H, 2 J H,H = 15.0 Hz, 2 J P,H = 11.3 Hz, CH 2 ); 13 C{ 1 H} NMR (CDCl 3 ) δ 2.6 (d, 3 J P,C = 3.2 Hz, SiMe 3 ), 2.9 (d, 3 J P,C = 1.9 Hz, SiMe3), 35.0 (d, 1 J P,C = 26.5 Hz, PCH 2 ), 43.3 (d, 1 J P,C = 12.9 Hz, PCH), 79.0−82.0 (m, C(CF 3 ) 2 ), 121.7 (q, 1 J F,C = 284.5 Hz, CF 3 ), 122.1 (qd, 1 J F,C = 285.5 Hz, 3 J P,C = 4.5 Hz, CF 3 ), 196.2 (dq sat , 1 J W,C = 126.1 Hz, 2 J P,C = 7.8 Hz, 6 J F,C = 1.5 Hz cis-CO), 199.0 (d, 2 J P,C = 31.0 Hz, trans-CO); 19 F NMR (CDCl 3 ) δ −76.3 (qd 4 J F,F = 9.9 Hz, 4 J P,F = 3.4 Hz), −77.8 (qd 4 J F,F = 9.9 Hz, 4 J P,F = 1.9 Hz). 29 Si NMR (CDCl 3 ) δ = 2.81 (d, 2 J P,Si = 6.8 Hz), -0.07 (d, 2 J P,Si = 7.6 Hz); 31 P{ 1 H} NMR (CDCl 3 ) δ 198.2 ppm (s sat , 1 J W,P = 297.6 Hz).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Similarly, 1,2-oxaphosphetane complexes III were unknown, and only one attempt was described, proposing a 1,2-oxaphosphetane complex as a reactive intermediate, but leading finally to a mixture of a phosphirane and a dioxaphospholane complex. 2 In recent years, we demonstrated that Li/Cl phosphinidenoid complexes are versatile building blocks leading to various new ring systems with aldehydes, 3 ketones, 4 imines, 5 or alkynes. 3 However, also 1,1′-bifunctional acyclic complexes were obtained in good yields and with high selectivity by formal insertion into the O−H bond of alcohols.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation